1999
DOI: 10.1055/s-2008-1072230
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Therapy for Pediatric Hepatoblastoma: Prevention and Treatment of Pulmonary Metastasis

Abstract: Our results of treatment for pediatric hepatoblastoma are presented with special emphasis on pulmonary metastasis. The pulmonary metastasis rate of hepatoblastoma was 44% (11/25). In 19 patients with resected hepatoblastomas, the 5-year survival rate without pulmonary metastasis was 90% (9/10); while with pulmonary metastasis it was 22% (2/9). Six patients with unresected hepatoblastomas all died within 4 months regardless of chemotherapy and/or metastasis. To improve survival in patients with hepatoblastoma, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
(39 reference statements)
1
8
1
Order By: Relevance
“…We observed metastases in both the liver and the lung in 50% (three out of six) of the successfully established PDTXs. The metastatic disease we observed is similar to human clinical data, where 46% HB and 44% HCC patients develop metastatic disease, primarily in the lung [33,34]. We also demonstrated that the orthotopic PDTXs preserve tumor heterogeneity not only within the primary xenograft but, intriguingly, also within specific metastases.…”
Section: Discussionsupporting
confidence: 85%
“…We observed metastases in both the liver and the lung in 50% (three out of six) of the successfully established PDTXs. The metastatic disease we observed is similar to human clinical data, where 46% HB and 44% HCC patients develop metastatic disease, primarily in the lung [33,34]. We also demonstrated that the orthotopic PDTXs preserve tumor heterogeneity not only within the primary xenograft but, intriguingly, also within specific metastases.…”
Section: Discussionsupporting
confidence: 85%
“…46% and 44% of human HCC and HB patients, respectively, have metastatic disease, primarily in the lung (38, 39). As was the case for the primary Tg-β-cat S tumors, we observed robust β-catenin expression in a lung metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…While early case reports showed the potential for cure following metastasectomy, initial chemotherapy trials also showed the possibility of complete resolution of lung metastases with chemotherapy alone. Two larger Japanese trials showed the importance of this combined approach and emphasized the use of metastasectomy for residual lung disease after chemotherapy 65, 66 . The strategy of combining chemotherapy and metastasectomy for residual disease is still used in all major hepatoblastoma cooperative trials for patients with pulmonary metastatic disease at diagnosis.…”
Section: Hepatoblastomamentioning
confidence: 99%